2015
DOI: 10.1108/oir-10-2014-0255
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-word-of-mouth performance in different psychological distances and familiarity

Abstract: Does organizational citizenship behavior add value to human interaction with e-services?", Online Information Review, Vol. 39 Iss 4 pp. -Access to this document was granted through an Emerald subscription provided by emerald-srm:463575 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Specifically, tourists' perceived images of Southern Xinjiang have a significant negative impact on their sense of psychological distance from Southern Xinjiang, which means that, as the perceived image of the tourist destination is improved, the tourists' sense of psychological distance will gradually decrease. Second, the result shows that tourists' sense of psychological distance from Southern Xinjiang has a significant negative effect on their travel intentions relating to Southern Xinjiang, which is consistent with previous studies (Hamilton, 2014;Tan & Chang, 2015). Finally, we should keep it in mind that the mediating role of the psychological distance is moderated by WOM.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, tourists' perceived images of Southern Xinjiang have a significant negative impact on their sense of psychological distance from Southern Xinjiang, which means that, as the perceived image of the tourist destination is improved, the tourists' sense of psychological distance will gradually decrease. Second, the result shows that tourists' sense of psychological distance from Southern Xinjiang has a significant negative effect on their travel intentions relating to Southern Xinjiang, which is consistent with previous studies (Hamilton, 2014;Tan & Chang, 2015). Finally, we should keep it in mind that the mediating role of the psychological distance is moderated by WOM.…”
Section: Discussionsupporting
confidence: 89%
“…The EWOM is an extension of traditional WOM in a virtual environment (Matute et al, 2016). According to the research of Tan and Chang (2015), the advantages of EWOM over the traditional WOM can be seen in the different scenarios generated by the psychological distance dimensions and destination familiarity. It is frequently ranked as the most influential source of repurchase information (Kim and Hardin, 2010) and, in this study, is incorporated in the dimension of customer loyalty, because positive EWOM influences customer behaviour, such as expenditure level and loyalty (Bowman and Narayandas, 2001;Godes and Mayzlin, 2004).…”
Section: Customer Loyaltymentioning
confidence: 99%
“…On the non-technical side, we are interested in defining metrics to analyze the achievements more deeply in relation to promoting reflection about cultural heritage, triggering curiosity and increasing retention. The grounds for such a study can be found in [26][27][28]. In particular, we want to gain insight into how those cognitive phenomena (and even emotional ones) can be fostered with a cross-border perspective by controversial characters or events that are viewed very differently in different countries, such as the figures of Gavrilo Princip (who is seen as a national hero by many in Serbia, whereas History textbooks in many other European countries present him as the villain who sparked the start of World War I) or Mustafa Kemal Atatürk (who was honored by UNESCO and the United Nations as a promoter of peace between nations, but is held responsible by many Greeks for acts of repression against minorities).…”
Section: Discussionmentioning
confidence: 99%